Hemolytic-uremic syndrome (HUS): a clinicopathological study of 15 cases - Tınaztepe, Keriman; Akkök, Nermin; Tınaztepe, Behçet (The Turkish Journal of Pediatrics, 1993)
Although hemolytic-uremic syndrome (HUS) is a clinico-pathological entity, renal biopsies are usually not indicated for diagnosis, and therefore, studies concerning the histological aspects of the syndrome are few. This study mainly describes the morphological characteristics of 15 tissue-diagnosed sporadic cases of HUS. The ages of the patients ranged between 10 mos. to 15 yrs., with five being under two. The male/female ratio was 2:3. The prodromal phase was present in 10 patients (67%) with gastrointestinal symptoms in four patients (27%) with neurological symptoms, and in three patients (20%) with upper respiratory infections. Five patients had HUS associated with diarrhea (D+) (three infants and two children), while the remaining ten patients (two infants and eight children) had no diarrhea (D−). E.coli was identified in the stool of four of the D+ cases, one of which was also associated with Shigella. The shortest clinical course was 14 days and the longest 55 days in 13 patients. The disease recurred after three months in one patient, and on three occasions in 15 months after onset of HUS in the other.Fourteen patients died and one biopsy-diagnosed case recovered after the acute phase. All patients had anemia (Hb 3.4-10 g/dl) and acute renal failure. Seven cases demonstrated Burr cells, eight cases had thrombocytopenia and six cases oliguria/anuria. Microscopic hematuria was detected in four cases and gross hematuria in two cases. All patients revealed proteinuria and azotemia (40-200 mg/dl).Five/five (100%) cases had decreased creatinine clearance, 12/14 (86%) cases had increased uric acid levels, 9/14 (64%) cases had an electrolyte imbalance.Light microscopy revealed microangiopathic type involvement of the glomeruli in all cases. According to additional findings, the cases were classed into three histological groups: type 1 showing cortical necrosis (3 cases), type 2 predominant glomerular and arteriolar involvement (11 cases) and type 3 predominant arterial involvement (1 case). All cases were considered primary HUS except for one which was associated with membranous glomerulonephritis. (D+) HUS cases were predominantly of the microangiopathic type, similar to the (D−) group; the latter being contrary to the literature. Hypertension was present in 67% of cases and there was no correlation found between the clinical duration of HUS and the histological type. All five patients studied immunohistologically revealed a nonspecific type fibrinogen deposition. Extra-renal microangiopathy was demonstrated in the adrenals, stomach, pancreas, liver and skin in two necropsies studied.
Keywords: hemolytic-uremic syndrome; thrombotic microangiopathy; acute renal failure